Anti-Inflammatory Activity of Compounds Isolated from Plants - R.M. Perez G. (The Scientific World Journal)
This review shows over 300 compounds isolated and identified from plants that previously demonstrated anti-inflammatory activity. They have been classified in appropriate chemical groups and data are reported on their pharmacological effects, mechanisms of action, and other properties.